Adaptability and phenotypic stability of sugarcane clones - Antunes, William Rodrigues; Schöffel, Edgar Ricardo; Silva, Sergio Delmar dos Anjos e; Eicholz, Eberson; Härter, Adílson (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to assess the adaptability and stability of sugarcane (Saccharum spp.)clones of mid‑late cycles, for their stem and sugar production, and their efficiency of solar energy conversion, in the northwestern region of the state of Rio Grande do Sul, Brazil. Thirteen clones were evaluated in nine environments, in a randomized complete block design, with three replicates. The variables used for the analysis of additive main effects and multiplicative interactions (AMMI) were: the stem and sugar productivity, and the efficiency of solar energy conversion. There was interaction between clones and environments, and the RB996527 clone stood out for its broad adaptation to test environments, high productivity of stalks and sugar, stability, and efficiency of solar energy conversion, having surpassed the control RB867515. The higher productivity environments were São Luiz Gonzaga (first ratoon) and Santa Rosa (plant cane and first ratoon).